Взаємодія магнітних наночастинок з клітинами - Turanska, S. P.; Kusyak, A. P.; Turov, V. V.; Gorbyk, P. P. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2013)
The review of articles has been carried out on the study of dependency onto living cells of the nano-sized magnetic particles, the conditions of getting them biocompatible, the application areas. The data are cited about mechanisms of cytotoxicity, its dependence on chemical composition, the sizes, concentration of nanoparticles, the type of protective cover, and also the biodegradation of nanomaterials in vivo and in vitro.